Analyzing Santri Perceptions of the Readability and Comprehension of Classical Islamic Texts in Khat Naskhi - Aslihah, Indy; Angela, Selvia; Faruq, Ahmad Umar (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2025)
Classical Islamic texts remain the cornerstone of Islamic education in pesantren (Islamic boarding schools), yet their readability poses a significant challenge, particularly for novice santri. This difficulty stems not only from the linguistic complexity of classical Arabic but also from the visual characteristics of the script (khat) used in printing. This study aims to analyze the perceptions of santri regarding the readability and comprehension of classical Islamic texts written in khat Naskhi at the Qur'anan 'Arobiyya Islamic Boarding School in Kediri, Indonesia. Khat Naskhi was selected for its clarity, proportionality, and widespread use in modern Qur’anic mushafs, making it a potential candidate for enhancing text accessibility. Employing a mixed-methods descriptive approach, data were collected through observation, semi-structured interviews, document analysis, and a questionnaire distributed to 55 respondents across various educational levels. The results indicate that 87% of santri found khat Naskhi easier to read, while 86% reported that it improved their understanding of the text. These findings underscore the significant influence of the visual aspect of script on the effectiveness of learning classical texts. However, a notable minority of santri perceived khat Naskhi as less representative of the traditional aesthetic and scholarly heritage associated with classical texts. This study concludes that while khat Naskhi is a highly effective tool for improving readability and comprehension for beginners, its adoption must be balanced with the preservation of traditional script forms to maintain the cultural and spiritual identity of pesantren education. The results provide a crucial foundation for the development of adaptive, user-centered learning media that are both pedagogically effective and culturally grounded.